Digital Akhlak: Menanamkan Etika Bermedia Sosial dalam Frame Pendidikan Agama Islam - Halimatus Sa’diyah Al-hasnah; Ijah Hodijah; Hilmi Maulana (Hikmah : Jurnal Studi Pendidikan Agama Islam, 2026)
The era of digital disruption has given rise to a moral crisis in cyberspace, where social media behavior is often detached from ethical values. Islamic Religious Education (PAI) has a significant responsibility to respond to this phenomenon so that religious teachings do not become merely static rituals, but rather dynamic guidelines in the digital world. Objective: This article aims to explore the concept of Digital Morals as a framework for social media ethics from an Islamic Religious Education (PAI) perspective. Method: This paper uses a critical analysis method by synthesizing religious texts (the Qur'an and Hadith) and contextualizing them with the reality of contemporary digital communication. Results: The analysis shows that the solution to digital moral decadence lies in internalizing the values ​​of Tabayyun, Siddiq, and Amanah as information filters. Digital Morals demands a transformation of the role of PAI from merely transferring knowledge to forming a sense of muraqabah (feeling God's supervision) in cyberspace. Conclusion: Through this analysis, it is concluded that Digital Morals within the PAI framework are not merely technical rules, but rather a form of social worship that is essential for realizing a healthy and civilized digital ecosystem. ​